Shockwave cardiac injury in thoracoabdominal gunshot wound - Ngwisanyi, Weludo (Int J Surg Case Rep, 2021)
INTRODUCTION AND IMPORTANCE: Cardiac injuries are associated with high mortality rates and most affected individuals succumb to their injuries before arrival to the hospital. Even though they have a higher fatality rate, penetrating cardiac injuries are relatively easy to diagnose and they have straightforward management protocols. On the other hand unexpected non-penetrating cardiac injuries, especially in haemodynamically stable patients, are not looked out for and can be difficult to diagnose. They may have a delayed presentation leading to poor patient outcomes. Clinicians should have a high index of suspicion when wound paths are in the vicinity of the heart, to avoid missing early signs and possibly prevent late presentation of these injuries. CASE PRESENTATION: Two previously well male patients aged 29 and 33 years old respectively, sustained gunshot wounds to the thoracoabdomen which in each case became associated with non perforating cardiac injuries. The first case highlighted the unfortunate end of these uncommon injuries when there are other serious injuries present. The second case illustrated possibility of late complications even after management of non-penetrating cardiac injury. CLINICAL DISCUSSION: In these cases, shock wave injury refers to non penetrating cardiac injury induced by high a voltage bullet in proximity to the heart/pericardium. A thorough history and examination in addition to multiple investigational modalities should be performed in order to exclude cardiac shockwave injuries. In some instances serial imaging studies are needed to detect the earliest changes associated with these injuries. CONCLUSION: Cardiac injuries carry a high morbidity and mortality and therefore a timeous diagnosis and management of these injuries is essential to prevent fatalities.